Front Desk Duty Multitasking Test After Mild Stroke: Preliminary Reliability and Validity. (December 2020) - Carroll, Ginger L.; Radomski, Mary; Halsten, Jerry; Meyers, Amy; Rabusch, Stacey; Takimoto, Romina; Kreiger, Robert
Background: Performance-based multitasking assessments may be more sensitive than cognitive screens to detect executive dysfunction after a mild stroke. Purpose: This cross-sectional study examined inter-rater reliability and preliminary convergent and discriminant validity of the Front Desk Duty Test (FDDT). Method: Adults with mild stroke ( n = 35) and community controls ( n = 33) were administered the FDDT and other measures of executive functions. Findings: Inter-rater reliability of the FDDT subscores were high (ICC 0.971–0.999). There were weak but statistically significant correlations between participants' scores on some of the executive function tests and some FDDT subscores. Participants with mild stroke and community controls had statistically significant different FDDT scores (performance accuracy p = .006; performance time, p = .033), with rank order FDDT score patterns across community controls, participants with mild stroke who passed the executive function screen, and participants with mild stroke who failed the executive function screen. Implications: Preliminary validation results suggest that the FDDT warrants further study.